2000
DOI: 10.1068/p3078
|View full text |Cite
|
Sign up to set email alerts
|

The Minimum Temporal Thresholds for Motion Detection of Grating Patterns

Abstract: The minimum temporal thresholds for absolute motion detection were measured for sinusoidal grating patterns in foveal vision. Test patterns of relatively low temporal frequencies and low velocities were examined. The thresholds clearly decreased with test velocities rather than with test temporal frequencies. Modified velocity-time reciprocity was observed (i.e. the relationship between test velocity and temporal thresholds was described by a simple equation including two constants which indicate temporal and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 29 publications
1
10
0
1
Order By: Relevance
“…The duration thresholds probably reflect both neural and stimulus limitations (Borghuis, 2003). Duration thresholds have been used in previous work on surround suppression (e.g., Betts, Taylor, Sekuler, & Bennett, 2005;Tadin & Lappin, 2005b;Tadin et al, 2003), on other aspects of motion perception (Mateeff, Dimitrov, & Hohnsbein, 1995;Tayama, 2000), color perception (Pokorny, Bowen, Williams, & Smith, 1979), and symmetry perception (Tyler, 2001). In the present study, the same method also measured spatial displacement thresholds.…”
Section: General Commentsmentioning
confidence: 89%
“…The duration thresholds probably reflect both neural and stimulus limitations (Borghuis, 2003). Duration thresholds have been used in previous work on surround suppression (e.g., Betts, Taylor, Sekuler, & Bennett, 2005;Tadin & Lappin, 2005b;Tadin et al, 2003), on other aspects of motion perception (Mateeff, Dimitrov, & Hohnsbein, 1995;Tayama, 2000), color perception (Pokorny, Bowen, Williams, & Smith, 1979), and symmetry perception (Tyler, 2001). In the present study, the same method also measured spatial displacement thresholds.…”
Section: General Commentsmentioning
confidence: 89%
“…These micromovements play an important role in counteracting neural adaptation [7]. However, drifts and microsaccades also cause retinal image slips that exceed the motion detection thresholds of humans [8]. Little is known about how the brain compensates for these small image slips.…”
Section: Introductionmentioning
confidence: 99%
“…Assuming that the refractoriness caused by a single flash lasts approximately 140 ms [20] and that the period of 12 Hz stimulation is ∼83 ms, the time window not covered by refractoriness is always ∼26 ms, which, in the case of either of the applied stimuli, appears to be too narrow for efficient processing. The minimum temporal threshold for form perception is definitely longer [26], and even if motion is processed more rapidly, thorough and well-documented studies found that the minimum is somewhere near 35 ms [27,28]. It is well known that the minimum temporal threshold for motion perception is influenced by stimulus speed.…”
Section: Discussionmentioning
confidence: 96%